1998
DOI: 10.1210/jcem.83.3.4624
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Intake and the Pattern of Thyroid Disorders: A Comparative Epidemiological Study of Thyroid Abnormalities in the Elderly in Iceland and in Jutland, Denmark

Abstract: Thyroid abnormalities are common in all populations, but it is difficult to compare results of epidemiological studies, because different methods have been used for evaluation. We studied the importance of the population iodine intake level for the prevalence rate of various thyroid abnormalities in elderly subjects. Random samples of elderly subjects (68 yr) were selected from the central person registers in Jutland, Denmark, with low (n = 423) and, in Iceland, with longstanding relatively high (n = 100) iodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(103 citation statements)
references
References 27 publications
9
85
0
4
Order By: Relevance
“…For many decades Iceland has been known for its high iodine status (5)(6)(7)23) . With the sharp decreases in milk and fish intakes during past decades, worries about iodine status in the population have increased (11,12,24) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many decades Iceland has been known for its high iodine status (5)(6)(7)23) . With the sharp decreases in milk and fish intakes during past decades, worries about iodine status in the population have increased (11,12,24) .…”
Section: Discussionmentioning
confidence: 99%
“…All European countries except Iceland have experienced this health and socio-economic threat to a greater or lesser extent (4) . The Icelandic population has in the past been known for its high iodine status, based on studies from 1939, 1988 and 1998 (5)(6)(7) . The good iodine status observed in these studies was suggested to be due to high fish consumption and abundant milk, both important dietary sources of iodine (8)(9)(10) .…”
mentioning
confidence: 99%
“…15 Iodine deficiency disorders abound in areas with inadequate iodine intake while autoimmune thyroid disorders are rare in iodine deficiency but become prevalent with transition to iodine sufficiency. 16 Monitoring disease patterns in Africa has proved challenging in the absence of 397…”
Section: Evolving Disease Patternsmentioning
confidence: 99%
“…Another survey in Italy found an overall prevalence of thyroid functional autonomy (i. e., subnormal TSH concentrations and normal concentration of FT3 and FT4) of 4.6 %. Finally, the overall prevalence of subclinical hyperthyroidism was lower in Spain (1.3 %) [24] and higher in Denmark (9.7 %) [25].…”
Section: Epidemiologymentioning
confidence: 84%